1991
DOI: 10.1007/bf01318203
|View full text |Cite
|
Sign up to set email alerts
|

Biliary pain in postcholecystectomy patients without biliary obstruction

Abstract: Biliary pain without obvious biliary obstruction is common in postcholecystectomy patients. We studied 20 symptomatic patients with episodes of biliary-type pain after cholecystectomy (all having undergone endoscopic retrograde cholangiography), and in 18 asymptomatic postcholecystectomy controls. We performed quantitative hepatobiliary radionuclide analysis with dimethyl-imidodiacetic acid. From a series of 90 dynamic images at 1-min intervals using a gamma camera coupled to a computer, time-activity curves w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Although initial experience was generally favourable (65-71), there was variability in the parameters used for scintigraphy and diagnostic criteria for SO dysfunction. Sphincterotomy has been shown to improve bile flow, often to normal values (68)(69)(70). One study (72) assessed many scintigraphic variables and found that the hepatic hilum to duodenal transit time is the best predictor of delayed bile flow into the duodenum.…”
Section: Mechanism Of So Dysfunctionmentioning
confidence: 99%
“…Although initial experience was generally favourable (65-71), there was variability in the parameters used for scintigraphy and diagnostic criteria for SO dysfunction. Sphincterotomy has been shown to improve bile flow, often to normal values (68)(69)(70). One study (72) assessed many scintigraphic variables and found that the hepatic hilum to duodenal transit time is the best predictor of delayed bile flow into the duodenum.…”
Section: Mechanism Of So Dysfunctionmentioning
confidence: 99%
“…This is a minimally invasive investigation that has the potential to provide useful data regarding flow dynamics across the SO. Initial studies did not show a strong correlation with either manometric findings or treatment outcome [25][26][27], but further refinements in the evaluation of the scintigraphic variables being analyzed have demonstrated correlation with SO manometry. As such, this investigation may be useful as a screening method for selecting patients for manometry [28,29].…”
Section: Diagnosis Of Sphincter Of Oddi Dysfunctionmentioning
confidence: 94%
“…administration of [99Tcm]‐diethyl iminodiacetic acid or a related compound and gives quantitative and qualitative information by measuring the time of the radionucleotide emptying from the liver and the biliary tract. Early studies were encouraging and suggested that it could replace SOM in the diagnosis of SOD 27–32 . Sostre et al 33 .…”
Section: Methodsmentioning
confidence: 99%